MEMBANGUN DEMOKRASI EKONOMI: STUDI POTENSI KOPERASI MULTI-STAKEHOLDERS DALAM TATA KELOLA AGRARIA INDONESIA - Dodi Faedlulloh (Masyarakat Indonesia, 2016)
As a country that once had the title of an agrarian country for most of its people are farmers, situation of agrarian in Indonesia shows the opposite. Land is the source of human life that was dominated by a handful of parties which cater to reach the coffers profit. The hope of the welfare of the people is still a problem that has not been completed. Social inequalities are becoming even rampant. The implication of social inequalities is agrarian conflicts in many regions of Indonesia. Resistance of the people in agrarian conflicts is getting bigger. This shows people's awareness of their rights. Agrarian governance in Indonesia has been stripped away the spirit of economic democracy initiated by the founding fathers. Therefore, the governance paradigm in agrarian must return to the spirit of economic democracy. The method used in this paper is the study of literature and using the phenomenological approach to make observations on the realities that are relevant to the assessment of the potential economic democracy in the governance of agrarian studies in Indonesia. All people have the right to have equal access and not to oppress in the use of agrarian resources. One form of the concrete actualization of economic democracy is by developing the cooperative as an alternative solution of agrarian governance in Indonesia. With multi-stakeholder cooperatives, agrarian reform can re-discover the substantive meaning, there is no longer a monopoly of the land and the people's welfare becomes possible.Keywords: Agrarian, Economic Democracy, Agrarian Conflict, Co-operative